2019
DOI: 10.3390/met9050565
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Simulated Study on Gas-Liquid Flow and Mixing Behavior in an ISASMELT Furnace

Abstract: In this study, a water-model experiment and numerical simulation were carried out in a pilot ISASMELT furnace to study the factors affecting mixing time. The experimental results were compared to the simulation results to test the accuracy of the latter. To study the internal factors that affect the mixing time, the turbulent viscosity and flow field were calculated using simulation. In addition, following previous research, external factors that influence the mixing time including the depth of the submerged l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…where S ij stands for the rate-of-strain tensor and is listed in Equation (10). α Ã and α Ã ∞ represent the constant with a value of 1 for high-Reynolds numbers flow.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where S ij stands for the rate-of-strain tensor and is listed in Equation (10). α Ã and α Ã ∞ represent the constant with a value of 1 for high-Reynolds numbers flow.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the requirement of a swirler in the application of the top blowing process is that the produced swirling flows can cool down the temperature of the pipe, increase the convective mixing and diffusion mixing efficiency of the fluid, enhance the radial stirring intensity for the liquid, and keep the sufficiently high axial momentum energy of the gas. [9][10][11] In fact, the annular pipe in the top blowing flow has a short service life with the failure model of the practical bending and tip burning [12] due to the insufficient protection of the swirling flow to the wall of the annular pipe. Thus, the optimization of the swirl-generating device is still a huge challenge, attributed to the limitation of the complex structure of the furnace, turbulent regime flow in-furnace, and the high temperature/pressure operating condition in the industrial equipment.…”
Section: Introductionmentioning
confidence: 99%
“…In the ISASMELT furnace, according to the CFD modeling work of Zhao et al, the mixing time generally decreases with an increasing gas flow rate (Zhao et al 2019b). A noteworthy point is that, in this case, as the gas flow rate increased to a certain range, mixing would become relatively slow.…”
Section: Modeling Approachesmentioning
confidence: 97%
“…A two-phase, top-blown ISASMELT furnace was modeled using CFD simulation by Zhao et al in 2019(Zhao et al 2019b). Different submersion depths and lance diameters were analyzed in order to optimize the lance arrangement.…”
Section: Modeling Approachesmentioning
confidence: 99%
“…Through CFD simulations, Obiso et al (2019) showed that density, viscosity and surface tension of liquid, injection gas rate and lance were key factors influencing operations of TSL furnaces. Zhao et al (2019) carried out water modelling and CFD simulations and found that the bath mixing time in a TSL furnace was controlled by liquid velocity and turbulence viscosity, and that an injection lance with swirl plate gave slightly longer mixing times than that without swirl plate.…”
Section: Introductionmentioning
confidence: 99%